111 RARE BUT FATAL COMPLICATION OF WARFARIN: SKIN NECROSIS. Issue 1 (1st January 2007) - Bansal, G.; Godkar, D.; Nesa, M.; Fernandez, G.; Niranjan, S.
Abstract : Introducton: Warfarin-induced skin necrosis (WISN) is a rare, but well-recognized, skin and soft tissue complication of oral anticoagulation therapy. Early recognition and treatment are necessary to avoid significant long-term morbidity. We present a case of WISN who presented to the hospital on the ninth day after the start of Coumadin, diagnosed promptly and treated successfully. Case Report: A 76-year-old woman with SLE was started on Coumadin for paroxysmal atrial fibrillation. She presented to the ER on the ninth day after starting Coumadin with an area of spontaneous ecchymosis on the right breast. She denied any injury to the affected area. INR on admission was 4.1, so Coumadin-related coagulopathy was suspected, Coumadin was withheld, and fresh frozen plasma infusion was planned. However, the patient, being a Jehovah's Witness, refused any kind of blood product transfusion, so vitamin K was administered to reverse the effect of Coumadin. However, on assessment by hematology, the diagnosis of WISN was entertained and low-molecular-weight heparin (LMWH) was started to prevent the skin from further damage and possibly restore the viable skin. After 2 days, the patient started to show improvement of the necrosed skin area and no new lesion was noticed. She was discharged home on LMWH. She is currently being followed up in the hematology clinic, is still on LMWH, and further workup, including protein C and S levels, is contemplated after LMWH is stopped. Discussion: Coumadin is used very extensively these days in clinical practice for numerous indications. The major complication and risk associated with its use is bleeding. Uncommonly in patients with protein C or S deficiency, Coumadin use may precipitate fatal widespread skin complications secondary to microvascular thrombi. Patients with WISN are typically middle-aged obese women receiving oral anticoagulation for thromboembolic events. Commonly involved sites include the breast, buttocks, and thighs. But cases involving the extremities, face, and trunk have also been reported. Although WISN usually occurs within 10 days of the start of warfarin therapy, with peak occurrence between days 3 and 6, sporadic cases of WISN have been reported after several years of Coumadin use, the longest recorded period being 15 years. Diagnosing WISN is very challenging because it may mimic multiple other conditions. Clinical history and cutaneous distribution is the major assistance in distinguishing WISN from other conditions. It is usually a diagnosis of exclusion. WISN is associated with very high morbidity that may require surgical intervention with débridement and skin grafting or even amputation. Death may result from failure to recognize and diagnose these complications at an early stage.